2019
DOI: 10.1200/jop.18.00483
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticancer Therapy: Management of Drug Interactions

Abstract: Oral anticancer therapy is increasingly integrated into the care of patients with cancer. Recognition and management of drug-drug interactions (DDIs) is critical to providing efficacious and safe anticancer treatment. DDIs with QTc-prolonging agents, anticoagulants, enzyme inducers and inhibitors, antidepressants, and acid suppressants are commonly encountered with anticancer therapies. Here, we review frequently observed DDIs and outline literature-supported suggestions for their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…For vasomotor symptoms the pharmacological options include selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors, clonidine and gabapentin. Clinicians should be aware of potential drug interactions with anticancer and adjuvant therapies (eg, see refs 21 22). Cognitive behavioral therapy may also improve menopause symptoms 23.…”
Section: Introductionmentioning
confidence: 99%
“…For vasomotor symptoms the pharmacological options include selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors, clonidine and gabapentin. Clinicians should be aware of potential drug interactions with anticancer and adjuvant therapies (eg, see refs 21 22). Cognitive behavioral therapy may also improve menopause symptoms 23.…”
Section: Introductionmentioning
confidence: 99%
“…Based on manual pharmacist review, 7% of subjects had a DDI that was considered clinically relevant, further supporting the conclusion that improved DDI screening is necessary to prevent harm in clinical trial subjects and ensure accuracy of trial data. The vast majority of DDI detected in these trial subjects were DDI that prevent drug absorption [17]. Absorption DDI are common for oral medications, which are being used more often in cancer treatment due to their improved convenience over parenteral administration [18].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that approximately 23% of cancer patients are reported to receive TKIs and PPIs concomitantly raises concerns around the clinical significance of this interaction [ 21 ]. A few reviews evaluated the clinical effect of this drug interaction and a similar consensus of mixed evidence was found [ 22 24 ]. For example, one study showed a negative effect on survival with concomitant use of acid suppressing agents and erlotinib [ 25 ].…”
Section: Introductionmentioning
confidence: 92%